Development of Flavor Variants and Packaging in the Fish Processing Community in Perancak Village, Jembrana District, Jembrana Regency, Bali - Ni Made Ayu Suardani Singapurwa; I Putu Candra; , I Nyoman Rudianta; Ni Komang Armaeni (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Pedetan" is a kind of food product made of dried fish with traditional Balinese spices which are manufactured by people in the Jembrana Regency, Bali. It is made from lemuru fish (Sardinella Lemuru) which is mostly produced in the coastal areas of Jembrana Regency. "Pedetan" is also one of the superior products from the Jembrana area, because it is one of many authentic foods of Jembrana. The development of traditional manufacturing was carried out with several improvements by applying basic feasibility in food processing. However, a study for business development and product marketing development on aspects of quality management and safety of raw materials and products was necessary to be conducted. The improvement was carried out in several sequenced activities starting from the processing step, so that the community could apply the technology being shared and was able to handle problems in the production of "Pedetan". After that, knowledge sharing on kinds of good processing methods, sanitation, and hygiene was done. Furthermore, the improvement also covered quality control starting from the selection of raw materials to the distribution of food products. Everything had been made sure to be carried out properly. The improvement of the production method managed to produce several product variants, decent packaging, and labeling. Based on the results of community service activities, new flavor variants were created which made it into 6 flavor variants in total, namely the original flavor, the Balado flavor, the sweet spicy flavor, the sweet flavor, the silver herring fish variant, and the cutlassfish variant.